2019
DOI: 10.1039/c9nj01859j
|View full text |Cite
|
Sign up to set email alerts
|

Aluminium complex-catalysed hydroboration of alkenes and alkynes

Abstract: Catalytic hydroboration of terminal alkenes/alkynes with HBpin using the Al(III) catalyst, [κ2-{Ph2P(=Se)NCH2(C5H4N)}Al(CH3)2] (1), under mild and solvent-free conditions to afford corresponding alkyl/alkenyl boronate esters in high yield is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 44 publications
2
22
0
Order By: Relevance
“…Together with the transition metal-free organocatalysts for the hydroboration of alkynes, environmentally benign and commercially useful main-group catalysts based on Al, 90,[130][131][132][133][134][135][136][137][138][139] Li, [138][139][140][141][142] and Mg 143,144 have been recently developed as alternatives to transition metal catalysts. 145 In 2016, Roesky et al reported the cis-hydroboration of alkynes catalyzed by a neutral DEP NacNacAlH 2 (18).…”
Section: Hydroborationmentioning
confidence: 99%
See 1 more Smart Citation
“…Together with the transition metal-free organocatalysts for the hydroboration of alkynes, environmentally benign and commercially useful main-group catalysts based on Al, 90,[130][131][132][133][134][135][136][137][138][139] Li, [138][139][140][141][142] and Mg 143,144 have been recently developed as alternatives to transition metal catalysts. 145 In 2016, Roesky et al reported the cis-hydroboration of alkynes catalyzed by a neutral DEP NacNacAlH 2 (18).…”
Section: Hydroborationmentioning
confidence: 99%
“…90 The working mode of 20 in the hydroboration of terminal alkynes is assumed to involve aluminum acetylide species 20a, which is the same as that proposed by Roesky. 90 However, the mechanism of the internal alkyne hydroboration is presumed to be associated with insertion of the alkyne into the Al-H bond of Together with a range of bidentate Al hydroboration catalysts, 90,130,131,133 Cowley recently communicated a series of new aluminium dihydride complexes with bidentate N,P-ligands (22, 22 0 , and 22 00 ) as the alkyne hydroboration catalyst. 134 These dihydride species (10 mol%) were found to catalyze the hydroboration of phenylacetylene at 110 C to give the trans-vinylboronate ester with excellent b-selectivity in good yields.…”
Section: Hydroborationmentioning
confidence: 99%
“…Recently, our working group demonstrated successfully that an aluminum metal catalyst [k 2 -{C 6 H 4 NCH 2 NP(Se)Ph 2 }Al(Me) 2 ] can be employed for the chemoselective hydroboration of alkenes and alkynes under mild conditions. [33] Later, our group also reported the use of a Ti IV complex, [{Ph 2 P(BH 3 ) N} 2 C 6 H 4 Ti(NMe 2 ) 2 ], as an efficient catalyst in the facile hydroboration of terminal alkynes under mild conditions to yield corresponding alkenyl borane products in good quantity. [34] Here, we report the use of an easily accessible, non-toxic, and environment-friendly catalyst, neosilyllithium (LiCH 2 SiMe 3 ), in the hydroboration of alkynes and alkenes in the presence of HBpin to generate a broad scope of alkyl boronic ester products in excellent yields under lenient conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Halide, alkyl, and hydride substituted group 13 metal complexes are widely used as catalysts in Lewis acid mediated reactions for example Friedel-Craft and Diels-Alder reaction, 30,31 initiator for cationic polymerization, 32 hydroboration, [33][34][35] hydro functionalization, 36 and epoxidation of alkenes. 37 In this regard, the cationic complexes are also of great interest due to increased electrophilicity resulting from the cationic charge, possibly enhance the substrate coordination and activation.…”
Section: Introductionmentioning
confidence: 99%